Comparative Evaluation of Regulation and Law Enforcement of Corruption Crimes in Indonesia and Malaysia - Ridwan Anthony Taufan; Erry Ariany; Ade Saptomo (Sociological Jurisprudence Journal, 2025)
The research compares the legal system of corruption between Indonesia and Malaysia, focused on legislation, law enforcement agencies, evidentiary mechanisms, and the application of sanctions against perpetrators of corruption. Although both countries have similarities in classifying corruption as a serious criminal offense, the application of different legal systems, namely civil law in Indonesia and common law in Malaysia, has a significant impact on the effectiveness of law enforcement. Indonesia has more regulations addressing corruption offenses, in addition to law enforcement bodies like the Corruption Eradication Commission (KPK), which possesses wider authorities. In contrast, Malaysia depends on the Suruhanjaya Pencegahan Rasuah Malaysia (SPRM), which has restricted powers in prosecution. These differences are reflected in the sanction application, the reverse proof system, and the judicial mechanisms used in each country. This research is expected to provide insight into the effect of legal system differences on corruption eradication in the two countries.